Applications of Microbial β-Mannanases - Dawood, Aneesa; Ma, Kesen (Frontiers in Bioengineering and Biotechnology, 2020)
Mannans are main components of hemicellulosic fraction of softwoods and they are present widely in plant tissues. β-mannanases are the major mannan-degrading enzymes and are produced by different plants, animals, actinomycetes, fungi and bacteria. These enzymes can function under conditions of wide range of pH and temperature. Applications of β-mannanases have therefore, been found in different industries such as animal feed, food, biorefinery, textile, detergent and paper and pulp. This review summarizes the most recent studies reported on potential applications of β-mannanases and bioengineering of β-mannanases to modify and optimize their key catalytic properties to cater to growing demands of commercial sectors.